Overleveraging in the banking sector: Evidence from Europe - Frauke Schleer; Willi Semmler; Julian Illner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Overleveraging of the banking sector has been considered as one of the main causes of the 2007-09 financial crisis and the subsequent great recession. It was also of major concern for the subsequent BIS regulatory policies resulting in Basel III and its request for higher capital requirements. It has now become highly relevant for the planned European banking union. Overleveraging of the banking sector exposes the financial sector and the macroeconomy to vulnerabilities, but also, as critics state, seems to constrain credit flows to the private sector. We present here a measure of overleveraging, defined as the difference of actual and sustainable debt, conduct an empirical study on overleveraging for 40 banks in Europe, and study the vulnerabilities and credit contractions that can arise subsequently. Before the year 2004 overleveraging has not been a serious problem as leverage was on a sustainable level. However, in the run-up to the financial crisis, actual and optimal debt ran apart and the banking sector began to suffer from overleveraging. We use a nonlinear Vector STAR model to evaluate the hypothesis that periods of increasing debt levels are accompanied by more severe credit constraints than periods of low leveraging. We demonstrate this for country groups across Europe.
Keywords: C61; E32; G01; 330; Overleveraging; banking sector; Vector STAR; real economy; credit flows; regime switch